2013
DOI: 10.1007/s00253-013-4759-3
|View full text |Cite
|
Sign up to set email alerts
|

Identification of an exo-ß-1,3-d-galactanase from Fusarium oxysporum and the synergistic effect with related enzymes on degradation of type II arabinogalactan

Abstract: An exo-ß-1,3-D-galactanase (Fo/1,3Gal) was purified from the culture filtrate of Fusarium oxysporum 12S. A cDNA encoding Fo/1,3Gal was isolated by in vitro cloning. Module sequence analysis revealed a "GH43_6" domain and a "CBM35_galactosidase-like" domain in Fo/1,3Gal. The recombinant enzyme (rFo/1,3Gal) expressed in Pichia pastoris degraded ß-1,3-galactan and ß-1,3-galactobiose (Gal2), and released only galactose (Gal). In contrast, the enzyme did not hydrolyze p-nitrophenyl ß-D-galactopyranoside, ß-1,4-Gal2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 34 publications
0
12
0
Order By: Relevance
“…To date, all characterized exo-␤-1,3-galactanases have greater activity toward ␤-1,3-galactan than ␤-1,3/␤-1,6-galactan from Prototheca zopfii, LWAG, gum arabic, and radish roots (1,(3)(4)(5)(6)(7)21). BLLJ_1840 has low sequence identities (27% to 28%) with other exo-␤-1,3-galactanases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, all characterized exo-␤-1,3-galactanases have greater activity toward ␤-1,3-galactan than ␤-1,3/␤-1,6-galactan from Prototheca zopfii, LWAG, gum arabic, and radish roots (1,(3)(4)(5)(6)(7)21). BLLJ_1840 has low sequence identities (27% to 28%) with other exo-␤-1,3-galactanases.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, exo-␤-1,3-galactanase hydrolyzes the ␤-1,3-galactan backbone, bypassing ␤-1,6-galactan side chains, and consequently releases galactose, ␤-1,6-galactooligosaccharides, and their derivatives (1,2). Exo-␤-1,3-galactanases, which belong to glycoside hydrolase family 43 (GH43), have been cloned and characterized from several sources, including bacteria and fungi (1,(3)(4)(5)(6)(7).…”
mentioning
confidence: 99%
“…Previously, we isolated, cloned, and characterized various GA-degrading enzymes from Fusarium oxysporum 12S, a phytopathogenic fungus that can grow using GA as the sole carbon source ( 14 , 15 , 16 , 17 , 18 ). In addition to these enzymes, we recently observed that Rha was released from GA by the culture supernatant of this fungus.…”
mentioning
confidence: 99%
“…To elucidate the detailed structure and modify the physical properties of GA, we obtained various AG‐II‐degrading enzymes such as β‐1,6‐galactanase [15], β‐ l ‐arabinopyranosidase [16], exo‐β‐1,3‐galactanase [17], α‐ d ‐galactopyranosidase [11], and α‐ l ‐arabinofuranosidase (unpublished result) from F. oxysporum 12S. When GA was degraded with an F. oxysporum 12S culture supernatant, an oligosaccharide was detected that differed from the reaction products obtained by the above enzymes.…”
Section: Introductionmentioning
confidence: 99%